Identification of depot-specific human fat cell progenitors through distinct expression profiles and developmental gene patterns - Tchkonia, Tamara; Lenburg, Marc; Thomou, Thomas; Giorgadze, Nino; Frampton, Garrett; Pirtskhalava, Tamar; Cartwright, Andrew; Cartwright, Mark; Flanagan, John; Karagiannides, Iordanes; Gerry, Norman; Forse, R. Armour; et al. (American journal of physiology: endocrinology and metabolism, 2007)
1 Obesity Research Center, 2 Department of Medicine and Department of Genetics and Genomics, Boston University, Boston, Massachusetts; 3 Department of Surgery, Creighton University, Omaha, Nebraska; 4 Division of Gastroenterology, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston Massachusetts; and 5 Mayo Clinic Foundation, Rochester, Minnesota Submitted 26 April 2006 ; accepted in final form 6 September 2006 Anatomically separate fat depots differ in size, function, and contribution to pathological states, such as the metabolic syndrome. We isolated preadipocytes from different human fat depots to determine whether the basis for this variation is partly attributable to differences in inherent properties of fat cell progenitors. We found that genome-wide expression profiles of primary preadipocytes cultured in parallel from abdominal subcutaneous, mesenteric, and omental fat depots were distinct. Interestingly, visceral fat was not homogeneous. Preadipocytes from one of the two main visceral depots, mesenteric fat, had an expression profile closer to that of subcutaneous than omental preadipocytes, the other main visceral depot. Expression of genes that regulate early development, including homeotic genes, differed extensively among undifferentiated preadipocytes isolated from different fat depots. These profiles were confirmed by real-time PCR analysis of preadipocytes from additional lean and obese male and female subjects. We made preadipocyte strains from single abdominal subcutaneous and omental preadipocytes by expressing telomerase. Depot-specific developmental gene expression profiles persisted for 40 population doublings in these strains. Thus, human fat cell progenitors from different regions are effectively distinct, consistent with different fat depots being separate mini-organs. visceral fat; homeotic genes; telomerase; metabolic syndrome Address for reprint requests and other correspondence: J. L. Kirkland, Boston University Medical Center, 88 East Newton St., Boston, MA 02118